Loss to follow-up associated factors in patients with chronic pulmonary aspergillosis and its impact on the disease prognosis - Shaoqiang Li; Ya Li; Zhengtu Li; Xin Yang; Yangqing Zhan; Weilong Li; Ye Lin; Feng Ye (Frontiers Media S.A., 2022)
ObjectivePulmonary aspergillosis is a rare but challenging pulmonary disease. The conditions of patients with chronic pulmonary aspergillosis (CPA) can be even more complicated. The mortality rate of CPA remains high, and the prognostic factors are not well established due to a high proportion of loss to follow-up. In this study, we aim to explore factors associated with loss to follow-up in CPA patients and their impact on the disease prognosis after withdrawing anti-fungal treatments.MethodsPatients with confirmed CPA, who were admitted to the Department of Respiratory and Critical Care Medicine, the First Affiliated Hospital of Guangzhou Medical University from March 2017 to November 2019, were enrolled in this prospective study. The enrolled patients were followed up for 6 months after discharge. For loss to follow-up patients, the reasons for loss to follow-up and their prognosis after withdrawing anti-fungal treatments during loss to follow-up were recorded by telephone communication. Multivariate logistic regression analysis was performed to determine factors associated with loss to follow-up.ResultsThe 199 out of 298 screened patients were included in the study. Except for 67 cases with regular follow-up, the rest 132 cases were lost to follow-up. Factors, including age > 60 years (OR = 2.036, P = 0.03), monthly income ≤ $583 (OR = 5.568, P = 0.0001), education ≤ 6 years (OR = 7.474, P = 0.0001), and non-local residence (OR = 5.893, P = 0.0001) were associated with the loss to follow-up according to multivariate logistic regression analysis. The most common reasons for loss to follow-up were economic factors and clinic visit distance. The overall case fatality rate (CFR) within 180 days in patients with regular follow-up and patients who stopped anti-fungal treatment during the loss to follow-up was 0% and 19.65%, respectively.ConclusionThe proportion of loss to follow-up in CPA patients remained high. Age (>60 years), poor financial status, low education, and non-local residence were the key factors associated with the loss to follow-up in this study. Our study reveals the need to optimize the follow-up procedures and improve the patients understanding about the benefits and limitations of follow-up to reduce the CFR.